Short contact with nickel causes allergic contact dermatitis - Ahlström, M. G.; Thyssen, J. P.; Menné, T.; Midander, K.; Julander, A.; Lidén, C.; Johnsen, C. R.; Johansen, J. D. (British journal of dermatology (1951), 2018)
Summary Allergic contact dermatitis is a common type of eczema that causes inflammation when skin comes into contact with certain substances. Although it is well accepted that long term skin contact can cause nickel allergy and dermatitis, the significance of relatively short and repeated nickel exposure in relation to induction and elicitation (i.e. first triggering) of nickel allergy has been less explored, and it has been proposed that short skin contact with nickel is safe. A study conducted in Denmark and Sweden attempted to test this proposition by examining whether repeated skin contact with nickel over short time periods would elicit allergic contact dermatitis. 16 adults who were known to have nickel allergy were tested along with a further 10 non‐allergic control subjects (a control subject is a healthy individual used for comparison). The subjects were exposed to nickel and aluminium discs on each forearm and each earlobe for 3 x 10 minutes. Also, one arm would be treated for 24 hours beforehand with 0.5% sodium lauryl sulfate (SLS) under occlusion (meaning the solution was applied then wrapped up with plastic wrap or cloth). SLS is added to bath products and detergents to make them foam and is a common cause of skin reactions. The purpose of this was to monitor differences in reactions to nickel in skin that was either normal or already irritated (by the SLS). Each nickel and aluminium site was evaluated and blood flow measured, as increased blood flow can show that skin is reacting to nickel. 62.5% of nickel allergic subjects reacted to nickel on the SLS treated arm. The nickel exposed skin also caused significantly more blood flow than aluminium exposed skin. No change in reactivity or blood flow was seen in any non‐SLS nickel exposed arms in nickel allergic patients, or in any control subjects. This study shows that relatively short repeated contact with nickel can elicit allergic contact dermatitis in irritated skin in people who already have a nickel allergy. The results support the restrictions in current nickel regulation. Linked Article: Ahlström et al. Br J Dermatol 2018; 179:1127–1134